PSYCHOACTIVE SUBSTANCES ABUSE TRENDS AMONG MEDICAL STUDENTS OF LAHORE; A CROSS SECTIONAL STUDY - Noshad, Maryam; Butt, Muhammad Hammad; Mehboob, Tooba; Bashir, Irfan; Aslam, Rabia; Tabassam, Naila (Pakistan Armed Forces Medical Journal, 2020)
Objective: To track the trends and patterns of psychoactive substance abuse among medical students.Study Design: Cross-sectional questionnaire based study.Place and Duration of Study: Medical Colleges and Universities of Lahore, from Aug to Sep 2019.Methodology: Total 200 medical students from Medical Colleges and Universities were included. The data wereanalyzed and computed using SPSS-21. Frequencies and percentages related to all the factors were computed.Results: Among study participants, 96 (48%) of males and 104 (52%) of females with 154 (77%) of these students belong to 21-25 years of age group. The observed prevalence of substance abuse among students was 42 (21%). Joy seeking and a friend’s offer was the initiation of psychoactive substance use among these students. Tobacco was the most highly consumed substance among students, followed by marijuana. Besides, the results also revealed that students also consumed cocaine and methamphetamine. Among 21% abusers, 4 (9%) and 5 (11%) of the students experienced side effects and withdrawal symptoms respectively.Conclusion: The increasing consumption of tobacco and indulgence in psychoactive drugs are concerning issues because of uncontrolled consumption can cause serious brain damage. Academic burden and stress are the mediators of drug abuse among students. Therefore, stress management training and workshops should be conducted in institutes.